The Changing Scenario in Afghanistan: Past, Present and Future - Muhammad Ismail (Genius Journals, 2021)
The United States and its allies have abandoned Afghanistan after a 20-year war in the world's most dangerous country. Throughout the country's history, Afghans have faced several wars as well as invasions by foreign countries. After Russia's invasion of Afghanistan in 1979-1990, the country's scenario will change. The United States creates many terrorist organizations across the world to aid Afghan people in their struggles against the Soviet Union, such as the Taliban, al Qaeda, and other minor groups. In Afghanistan, the major two parties, the Northern Alliance and the Taliban, are fighting for power and control. In 1996, the Taliban seized power in Afghanistan, and Mullana Umar became the new leader of the country. Following the terrorist attacks on September 11, 2001, the United States and its allies launched an assault on Afghanistan to overthrow the Taliban regime in Kabul. The Taliban’s' leaders segregated separate mountainous areas of the nation and began resistance against the United States and the Afghan government until 2021
Keywords: Afghanistan; USA; Taliban; Doha